Non-spousal Family Support, Marital Status, and Heart Problems in Adulthood - Chai, Hye Won (Psychol Health, 2020)
OBJECTIVES: Support from one’s spouse has long been documented as a significant determinant of health for married individuals. However, non-spousal family support may play an important role in health particularly for unmarried individuals. Therefore, this study examined whether the association between non-spousal family support and diagnosis of heart problems differed by marital status and whether gender and education moderated these associations. DESIGN: Data came from the first two waves of the Midlife in the United States (MIDUS) study. This study selected respondents who participated in both waves of MIDUS and were not diagnosed with a heart problem at Wave 1 (N = 3,119). MAIN OUTCOME MEASURES: Participants reported whether they had any heart trouble. Discrete-time event history analysis was used to examine the risk of heart problems between MIDUS Waves 1 and 2. RESULTS: A higher level of non-spousal family support was associated with a lower risk of developing a heart problem only among unmarried women and unmarried individuals with high school education or less, and not for married individuals. CONCLUSION: Findings highlight the importance of considering specific sources of family support when studying heart health, and the health-protective role of non-spousal family support for those who are not married.